Interaction of chemotherapy and radiotherapy in altering the shape of subcortical structures in patients with nasopharyngeal carcinoma - Nan, Feibiao; Gao, Jian-ming; Li, Li; Zhang, You-ming; Zhang, Yuanchao (Frontiers in Oncology, 2022)
Neuroimaging studies have found significant structural alterations of the cerebral cortex in patients with nasopharyngeal carcinoma (NPC) following radiotherapy (RT) or concomitant chemoradiotherapy (CCRT), while their effects on the shape of subcortical structures remain largely unknown. In this study, we investigated the subcortical shape alterations between three groups: 56 untreated NPC patients (pre-RT group), 37 RT-treated NPC patients (post-RT group), and 108 CCRT-treated NPC patients (post-CCRT group). Using FSL-FIRST, we found that, compared with the pre-RT group, the post-CCRT group exhibited significant inward atrophy in the bilateral thalamus, bilateral putamen, left pallidum, and left caudate and outward inflation in the left caudate, while the post-RT group only exhibited inward atrophy in the bilateral thalamus. In addition, greater maximum dosage of RT for temporal lobes was associated with more severe inward atrophy of the bilateral thalamus in treated NPC patients. These results indicated that there may be an interaction between RT and CT that can cause subcortical damage.